cos ( 7 π ) × cos ( 7 3 π ) × cos ( 7 5 π ) cos ( 7 2 π ) + cos ( 7 4 π ) + cos ( 7 6 π ) = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
cos ( π − A ) = − cos A ∴ cos ( 7 2 π ) + cos ( 7 4 π ) + cos ( 7 6 π ) = cos ( 7 2 π ) − cos ( 7 3 π ) − cos ( 7 π ) = − { cos ( 7 π ) − cos ( 7 2 π ) + cos ( 7 3 π ) } = − 2 1
A g a i n cos ( 7 π ) × cos ( 7 3 π ) × cos ( 7 5 π )
= cos ( 7 π ) × cos ( 7 3 π ) × ( − cos ( 7 2 π ) )
= − { cos ( 7 π ) × cos ( 7 2 π ) × cos ( 7 3 π ) }
= − 8 1
\thereforr / f = cos ( 7 π ) × cos ( 7 3 π ) × cos ( 7 5 π ) cos ( 7 2 π ) + cos ( 7 4 π ) + cos ( 7 6 π ) = 4 .
Proofs of blue formulae can be had from Google or yahoo. Below is one proof.
cos ( 7 π ) − cos ( 7 2 π ) + cos ( 7 3 π ) = 2 1 .
Multuiply and divide numerator of f by 2sin(2π}7 ,.......
and since sin(2A) = 2sinAcosA ... and 2sinAcosB = sin(A+B) + sin(A-B).....sin( π - A)=sinA.
Numerator of f
= 1/2sin(π/7) { 2sin(π/7)cos(π/7) + 2sin(π/7)cos(3π/7) + 2sin(π/7)cos(5π/7) }
= 1/2sin(π/7){ sin(2π/7) + sin(π/7+3π/7) + sin(π/7-3π/7) + sin(π/7+5π/7) + sin(π/7-5π/7) }
= 1/2sin(π/7){ sin(2π/7) + sin(4π/7) + sin(-2π/7) + sin(6π/7) + sin(-4π/7) }
= {sin(π/7)}/2sin(π/7)
= 1/2 .
cos ( 7 π ) × cos ( 7 2 π ) × cos ( 7 3 π ) = 8 1 .
Muliply denominator of f by 8 sin pi/7 ....... and sin( π - A)=sinA ...we get,
8 sin pi/7 cos pi/7 cos 2pi/7 cos 3pi/7 = 4(2 sin pi/7 cos pi/7 cos 2pi/7 cos 3pi/7) = 4( sin 2pi/7 cos 2pi/7 cos 3pi/7) ..........as sin 2A = 2 sin A cos A.
= 2( 2 sin 2pi/7 cos 2pi/7 cos 3pi/7)
= 2 ( sin 4pi/7 cos 3pi/7) = - 2 ( sin 4pi/7 cos 4pi/7 )...................as cos 3pi/7 = - cos 4pi/7 = - sin 8pi/7 = sin pi/7 .
So denominator of f
=cos pi/7 cos 2pi/7 cos 3pi/7 = 1/8.